A systematic review of balance and fall risk assessments with mobile phone technology. (November 2017) - Roeing, Kathleen L.; Hsieh, Katherine L.; Sosnoff, Jacob J.
Highlights: The systematic review evaluates mobile device applications that measure balance. 13 articles meeting our inclusion criteria were included in the review. A wide range of static and dynamic balance tests were used. Despite measuring balance, studies lack measures of validity and reliability. Applications should measure validity and consider user functionality in design. Abstract: Falls are a major health concern for older adults. Preventative measures can help reduce the incidence and severity of falls. Methods for assessing balance and fall risk factors are necessary to effectively implement preventative measures. Research groups are currently developing mobile applications to enable seniors, caregivers, and clinicians to monitor balance and fall risk. The following systematic review assesses the current state of mobile health apps for testing balance as a fall risk factor. Thirteen studies were identified and included in the review and analyzed based on study design, population, sample size, measures of balance, main outcome measures, and evaluation of validity and reliability. All studies successfully tested their applications, but only 38% evaluated the validity, and 23% evaluated the reliability of their applications. Of those, all applications were found to accurately and reliably measure balance on select variables. Four of the 13 studies included special populations groups. Out of the 13 studies, 12 reported clinicians as their intended user and seven reported seniors as their intended user. Further research should examine the validity of mobile health applications as well as report on the application's usability.